2015
DOI: 10.2147/ijnrd.s82419
|View full text |Cite
|
Sign up to set email alerts
|

Chronic peritoneal dialysis in children

Abstract: The incidence of end-stage renal disease in children is increasing. Peritoneal dialysis (PD) is the modality of choice in many European countries and is increasingly applied worldwide. PD enables children of all ages to be successfully treated while awaiting the ultimate goal of renal transplantation. The advantages of PD over other forms of renal replacement therapy are numerous, in particular the potential for the child to lead a relatively normal life. Indications for commencing PD, the rationale, preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 56 publications
(62 reference statements)
0
17
0
11
Order By: Relevance
“…PD-related peritonitis has decreased since the late 1980s; however, peritonitis remains the major complication of PD and the most common reason for changing dialysis modality [1, 5-7]. According to Standardizing Care to Improve Outcomes in Pediatric end-stage renal disease Collaborative, the global peritonitis incidence rate is 0.46 episodes per patient-year [8], while the North American Pediatric Renal Transplant Cooperative Study found 0.68 peritonitis episodes per patient-year in PD-treated children [9].…”
Section: Introductionmentioning
confidence: 99%
“…PD-related peritonitis has decreased since the late 1980s; however, peritonitis remains the major complication of PD and the most common reason for changing dialysis modality [1, 5-7]. According to Standardizing Care to Improve Outcomes in Pediatric end-stage renal disease Collaborative, the global peritonitis incidence rate is 0.46 episodes per patient-year [8], while the North American Pediatric Renal Transplant Cooperative Study found 0.68 peritonitis episodes per patient-year in PD-treated children [9].…”
Section: Introductionmentioning
confidence: 99%
“…Peritonitis is known to be a commonest complication of PD in many national 14,16 and international studies. 19,20 Catheter related complications are also very common in children undergoing PD. 11,15 Higher rates of peritonitis in comparison to present work have also been reported earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of peritonitis are also significantly higher. A 25-year study of infant dialysis reports an odds ratio of 19 ( p < 0.001) for peritonitis in patients with concurrent gastrostomies (12). Fungal peritonitis, although observed to be higher, was not statistically significant (13).…”
Section: Discussionmentioning
confidence: 99%